Nutritional support during the first week for infants with bronchopulmonary dysplasia and respiratory distress: a multicenter cohort study in China - Huijia Lin; Guannan Bai; Jiajing Ge; Xuefeng Chen; Xinyu He; Xiaolu Ma; Liping Shi; Lizhong Du; Zheng Chen (BMC, 2024)
Abstract Background Bronchopulmonary dysplasia (BPD) is a major complication affecting the survival rate and long-term outcomes of preterm infants. A large, prospective, multicenter cohort study was conducted to evaluate early nutritional support during the first week of life for preterm infants with a gestational age < 32 weeks and to verify nutritional risk factors related to BPD development. Methods A prospective multicenter cohort study of very preterm infants was conducted in 40 tertiary neonatal intensive care units across mainland China between January 1, 2020, and December 31, 2021. Preterm infants who were born at a gestational age < 32 weeks, < 72 h after birth and had a respiratory score > 4 were enrolled. Antenatal and postnatal information focusing on nutritional parameters was collected through medical systems. Statistical analyses were also performed to identify BPD risk factors. Results The primary outcomes were BPD and severity at 36 weeks postmenstrual age. A total of 1410 preterm infants were enrolled in this study. After applying the exclusion criteria, the remaining 1286 infants were included in this analysis; 614 (47.7%) infants were in the BPD group, and 672 (52.3%) were in the non-BPD group. In multivariate logistic regression model, the following six factors were identified of BPD: birth weight (OR 0.99, 95% CI 0.99-0.99; p = 0.039), day of full enteral nutrition (OR 1.03, 95% CI 1.02-1.04; p < 0.001), parenteral protein > 3.5 g/kg/d during the first week (OR 1.65, 95% CI 1.25-2.17; p < 0.001), feeding type (formula: OR 3.48, 95% CI 2.21-5.49; p < 0.001, mixed feed: OR 1.92, 95% CI 1.36-2.70; p < 0.001; breast milk as reference), hsPDA (OR 1.98, 95% CI 1.44-2.73; p < 0.001), and EUGR ats 36 weeks (OR 1.40, 95% CI 1.02-1.91; p = 0.035). Conclusions A longer duration to achieve full enteral nutrition in very preterm infants was associated with increased BPD development. Breastfeeding was demonstrated to have a protective effect against BPD. Early and rapidly progressive enteral nutrition and breastfeeding should be promoted in very preterm infants. Trial registration The trial was registered in the Chinese Clinical Trial Registry (No. ChiCTR2000030125 on 24/02/2020) and in www.ncrcch.org (No. ISRCTN84167642 on 25/02/2020).